PERAN GENERATIVE ARTIFICIAL INTELLIGENCE DALAM MENGEMBANGKAN KETERAMPILAN BERPIKIR KREATIF SISWA SEKOLAH DASAR: A SYSTEMATIC LITERATURE REVIEW - Nabila Putri Azzahra; Nadin Septiani; Siti Zahra; Riscka; Darwanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of generative artificial intelligence (generative AI) has created new opportunities to enhance the quality of learning in elementary schools, particularly in fostering students’ creative thinking skills. This study aims to analyze the implementation of generative AI through a Systematic Literature Review (SLR). The review followed the PRISMA guidelines, including identification, screening, eligibility assessment, and article inclusion. Literature was collected from Google Scholar, focusing on publications from 2025–2026. Of the 23 articles identified, 21 met the inclusion criteria, comprising 14 primary studies and 7 supporting studies. The findings indicate that generative AI promotes creative thinking through instructional approaches such as project-based learning, game-based learning, STEM, contextual teaching and learning, and digital scaffolding. In addition, generative AI enhances student engagement, conceptual understanding, and teachers’ instructional efficiency. However, its implementation is still challenged by limited teachers’ digital literacy, inadequate technological infrastructure, and the need for continuous professional development. Therefore, pedagogically appropriate integration of generative AI is essential to support innovative learning and the development of twenty-first-century competencies in elementary education.